Seismic effectiveness of hysteretic tuned mass dampers for inelastic structures. (1st August 2020) - Boccamazzo, Antonio; Carboni, Biagio; Quaranta, Giuseppe; Lacarbonara, Walter
Highlights: A novel hysteretic TMD for seismic control of nonlinear structures is examined. A steel frame structure and a masonry building are the considered case studies. The detrimental effect of detuning is directly taken into account. The optimization of the hysteretic TMD is performed via Differential Evolution. The hysteretic TMD works better than a classical linear one and is more robust. Abstract: The problem of reducing the damage due to seismic loads in engineering structures by means of tuned mass dampers (TMDs) is addressed. Differently from previous studies focused on linear or geometrically nonlinear TMDs, the present work is concerned with a device that exhibits a hysteretic restoring force with pinching. A numerical TMD optimization is carried out so as to ensure optimal energy transfer from the main structure to the TMD for various seismic ground motion severities. The effectiveness of the vibration protection strategy is discussed for two different structural systems, i.e. a multi-story steel building with a purely elastoplastic behavior and a masonry building that exhibits stiffness and strength degradation. Numerical simulations demonstrate that the hysteretic TMD can achieve a meaningful average reduction of the root mean square (RMS) displacement of the steel structure between 40% (for 1% mass ratio) and 60% (for 5% mass ratio). Various seismic records related to soil types and seismic intensity levels different from those considered at the design stage, or unpredictable variations of the main system stiffness up to 10%, are shown to have rather limited influence on the TMD performance. It is shown that a classical linear TMD can attain a protection level comparable to that of the hysteretic TMD only at the expense of much higher mass ratios. Compared to the multi-story structure, the performance of the hysteretic TMD in a masonry building is still satisfactory although degraded, i.e. by about 15% in terms of RMS displacement. The performance is better than that of a classical linear absorber for very small mass ratios, especially for mid- or high-intensity seismic ground motions. The greater robustness of the hysteretic TMD performance for a wide range of seismic ground motions is due to its softening-type backbone, which can be optimized to accommodate the frequency changes that engineering structures typically undergo under seismic excitation. The role of the pinching in the performance of the hysteretic TMD is clarified.